Preliminary findings of a randomized controlled trial investigating the efficacy of transcranial magnetic stimulation in treatment-resistant depression: a post-hoc analysis on the role of co-occurring personality disorders - Maciaszek, Julian; Rymaszewska, Joanna; Wieczorek, Tomasz; Piotrowski, Patryk; Szcześniak, Dorota; Beszłej, Jan A.; Małecka, Monika; Bogudzińska, Bogna; Senczyszyn, Adrianna; Siwicki, Damian; Biercewicz, Marta; Kowalski, Krzysztof; et al. (Frontiers in Psychiatry, 2024)
IntroductionDespite the high hopes for the use of transcranial magnetic stimulation (TMS) in the treatment of depression, between 30% and 60.5% of patients do not respond to stimulation. The factors contributing to non-response, especially those related to personality, remain insufficiently investigated. The main aim of our study was to compare the efficacy of active TMS and sham–placebo protocols in combined therapy of treatment-resistant depression with evaluation of possible personality disorders comorbidity.MethodsThe study was conducted between December 2019 and December 2022, as a randomized, double-blind, active comparator-controlled and sham-controlled parallel trial. Patients (n = 41) were randomized into one of two experimental conditions (active TMS vs. placebo) and screened before and after stimulation as well as at a 3-month follow-up. Personality disorders were assessed with The Structured Clinical Interview for DSM-5 Personality Disorders.ResultsThere were no significant differences between the TMS active and sham groups in terms of general characteristics, coexisting personality disorders, and Montgomery–Åsberg Depression Rating Scale scores before stimulation, at the end of stimulation, and after 3 months of stimulation. However, linear regression analysis revealed significant negative associations between the coexistence of personality disorders and the reduction of depressive symptoms from baseline to the end of stimulation. The post-hoc exploratory analysis on the first phase of the RCT confirmed the presence of personality disorders to be a consistent negative influence on the reduction of depressive symptoms post-stimulation, regardless of protocol and experimental condition and demonstrated a smaller percentage reduction in depressive symptoms after stimulation in patients with personality disorders.DiscussionA central conclusion, based on our study, is that transcranial magnetic stimulation for treatment-resistant depression cannot be considered as a method independent of co-occurring personality disorders.